Perlindungan Hukum Penerima Jaminan Fidusia Atas Barang Persediaan Dengan Surat Perintah Penyerahan (Delivery Order) Sebagai Bukti Kepemilikan Barang Jaminan - Sadewa, Rawikara Dhita; Daim, Nuryanto Ahmad; Ismono, Joko (Universitas Wijaya Putra, 2023)
When it comes to trading at the highest level, it cannot be separated from other industries, namely the financing industry, both by bank financial institutions and non-bank financing institutions. At the highest level traders who directly buy and sell with producers in need of substantial funds to make purchases even though their existence makes the purchase price that will be obtained of course be at the lowest level with the number of purchases at the highest level as well, so this is where the role of the financing industry, where financial institutions will support traders by providing loans or credit, of course, with a guarantee of certain repayment. This research uses normative juridical research so that it is expected that from this research the truth can be obtained based on the scientific logic of law from a normative side, especially with the considerations of the panel of judges in deciding case Number 781/Pdt.G.2015/PN.JKT.Sel. The research approach that will be used is the statutory approach (statute approach), concept approach and case approach. The results of this study found that in the Fiduciary UUJF the authors argue that there is no provision related to the guarantee of legal protection for special fiduciary recipients such as recipients of fiduciary guarantees whose fiduciary guarantee objects are not under the control of the owner or fiduciary giver because of the characteristics of a Delivery Order. Order) does not conflict with the provisions of article 1 UUJF.